Buying-shopping disorder—is there enough evidence to support its inclusion in ICD-11? - Müller, Astrid; Brand, Matthias; Claes, Laurence; Demetrovics, Zsolt; de Zwaan, Martina; Fernández-Aranda, Fernando; Frost, Randy O.; Jimenez-Murcia, Susana; Lejoyeux, Michael; Steins-Loeber, Sabine; Mitchell, James E.; Moulding, Richard; et al. (CNS spectrums, 2019)
The phenomenon of buying-shopping disorder (BSD) was described over 100 years ago. Definitions of BSD refer to extreme preoccupation with shopping and buying, to impulses to purchase that are experienced as irresistible, and to recurrent maladaptive buying excesses that lead to distress and impairments. Efforts to stop BSD episodes are unsuccessful, despite the awareness of repeated break-downs in self-regulation, experiences of post-purchase guilt and regret, comorbid psychiatric disorders, reduced quality of life, familial discord, work impairment, financial problems, and other negative consequences. A recent meta-analysis indicated an estimated point prevalence of BSD of 5%. In this narrative review, the authors offer a perspective to consider BSD as a mental health condition and to classify this disorder as a behavioral addiction, based on both research data and on long-standing clinical experience.